2021
DOI: 10.1002/micr.30714
|View full text |Cite
|
Sign up to set email alerts
|

Sacral defect reconstruction using a sensate superior gluteal artery perforator flap based on the superior cluneal nerves: A report of two cases

Abstract: The superior gluteal artery perforator (SGAP) flap is a widely used flap for sacral reconstruction. However, it is non‐sensate flap and sensory loss is one of the most important risk factors for pressure ulcer development and recurrence; therefore, a sensate SGAP flap would be ideal for the reconstruction. Because the upper buttock is innervated by the superior cluneal nerves (SCNs) which originate from Th11 to L4, a sensate SGAP flap based on SCNs is anatomically possible. Herein, we present a novel sensate S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 12 publications
0
7
0
Order By: Relevance
“…The superior gluteal artery shows fixed anatomical marks, low variation, convenient location, and rich blood supply, which provides an anatomical basis for the wide clinical application of the perforator flap 6 . Therefore, the superior gluteal artery perforator flap has been used in various forms to repair ischial and sacral pressure ulcers 24,28–30 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The superior gluteal artery shows fixed anatomical marks, low variation, convenient location, and rich blood supply, which provides an anatomical basis for the wide clinical application of the perforator flap 6 . Therefore, the superior gluteal artery perforator flap has been used in various forms to repair ischial and sacral pressure ulcers 24,28–30 …”
Section: Discussionmentioning
confidence: 99%
“…6 Therefore, the superior gluteal artery perforator flap has been used in various forms to repair ischial and sacral pressure ulcers. 24,[28][29][30] In our study, a superior gluteal artery perforator flap was recommended to repair pressure ulcers in the central region, which could be in the form of island clockwise or counterclockwise rotation or V-Y advancement, and the donor site was sutured directly. In some cases, when a single perforator flap is insufficient because of excessive tension at the donor site, 2 or even multiple perforator flaps can be used and assembled, effectively distributing the tension among multiple flaps for repair.…”
Section: Discussionmentioning
confidence: 99%
“…The posterior divisions of the lateral cutaneous branches of the intercostal nerves can be included in thoracodorsal artery perforator flaps and used for neural coaptations (Lin et al, 2009). Harvested nerves can have coaptation with the superior cluneal (Iida et al, 2021) or sacral nerves (Cheong et al, 2005), also known as sensory nerves that innervate the buttock area. However, considering that most of the recalcitrant sore patients are paraplegia due to cord injury, sensory innervation should be restored through microsurgical coaptation between a flap and a sensory nerve located cranial to the level of injury (Zwanenburg et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the above advantages, the LD musculocutaneous flap can also be used as a sensate flap. It is well known that the sensate flap for sacral sore is very useful surgical option to prevent pressure ulcer recurrence and delayed wound healing (Iida et al, 2021). The posterior divisions of the lateral cutaneous branches of the intercostal nerves can be included in thoracodorsal artery perforator flaps and used for neural coaptations (Lin et al, 2009).…”
Section: Casementioning
confidence: 99%
“…Although the free SCN‐innervated SGAP flap has been already reported for breast reconstruction (Blondeel, 1999), there is few previous report on the pedicled SCN‐innervated SGAP flap for sacral ulcer reconstruction. Iida et al reported SGAP flap based on SCNs (Iida et al, 2021). Their concept is the same as ours; however, there are some differences.…”
Section: Discussionmentioning
confidence: 99%